CP-100 Strategy for the simplification of antiretroviral therapy: protease inhibitor monotherapy. (24th February 2014) - Mañes, M; Moriel, C; Santaolalla, I; Garcia, JL; Martín, I; Segura, M
Abstract : Background: Treatment simplification with protease inhibitors (PI) boosted with ritonavir in HIV-infected adults is a growing strategy with a number of considerable advantages: it is a well-tolerated treatment that reduces side effects such as lipodystrophy and peripheral neuropathy associated with other antiretroviral therapy (ART). Other advantages include the reduced number of tablets to be taken, improved adherence and decreased healthcare cost. The disadvantage of this strategy is virological failure (VF) defined as a plasma HIV-1 RNA >50 copies/ml six months after starting treatment. Possible reasons for VF include poor adherence, low CD4 nadir, and the possibility of pre-existing PI resistance (mutations). Purpose: To analyse the efficacy and safety as well as the cost savings that PI simplification strategy provides in a General Hospital. Materials and methods: Retrospective study conducted of patients who changed from ART to PI from January to July 2012 with follow up until March 2013. The following parameters were obtained from the electronic medical record: age, gender, adherence and HIV RNA before and after the change of treatment, reason for change, failure of monotherapy, annual healthcare cost saving. Results: A total of 85 patients were eligible (median age 47.5 years (IQR:10.5) and 69% men). These patients were long-term virologically suppressed (>80% patients with negative viral load at at least 6 months, ) good adherence to ART (average 92%) and had no history of PI failure. The reasons for treatment change were: simplification of ART (73%), lipodystrophy (21%) and hepatic and renal toxicity (6%). Monotherapy consisted of darunavir/ritonavir for 79% and lopinavir/ritonavir for 21% Only 12 patients discontinued treatment: 4 of them due to interactions with tuberculosis drugs and addition of telaprevir to the treatment, 1 dropped out of treatment and 7 due to VF due to adherence rate less than 90% in monotherapy. All recovered virological control by adding nucleoside analogues, HIV RNA becoming undetectable in the 3 months following. The monotherapy improved adherence in 19 patients and represented a total annual saving of 3, 703 € per patient and 311, 084 € in total. Conclusions: Treatment with boosted PI monotherapy appears to be a promising strategy that has proven to be effective in clinical practice: 85.8% of our patients remained virologically controlled. The simplified treatment improves compliance and contains costs, becoming a cost effective therapeutic option in selected patients. No conflict of interest.